MR Pelvimetry for Breech Presentation at Term– Interobserver Reliability, Incidental Findings and Reference Values - von Bismarck, Amanda; Ertl-Wagner, Birgit; Stöcklein, Sophia; Schöppe, Franziska; Hübener, Christoph; Hertlein, Linda; Baron-Tomlinson, Dominique; Mahner, Sven; Delius, Maria; Hasbargen, Uwe; Franz, Marie (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
Purpose Antepartal MR pelvimetry is used to assess the viability of vaginal breech delivery. We evaluated the reliability of MR pelvimetric measurements as well as incidental findings noted by different clinicians and assessed potential reference values.Methods In this monocentric study, the radiologic database was searched for obstetric MR pelvimetries with singleton breech pregnancies between 1999 and 2016. 99 consecutive MR pelvimetries were included. A structured, independent review was performed by six observers with three clinical experience levels (attending, fellow, junior resident from the departments of radiology and obstetrics). Image analysis entailed the quantitative assessment of conjugata vera (CV) and diameter transversalis (DT), image quality and incidental findings. Obstetric data was retrieved from the obstetric database for reference value assessment.Results Interobserver agreement was strong throughout (mean intraclass correlation coefficient range: 0.889 – 0.968). The individual measuring biases ranged between 0 – 2 mm, and the average limits of agreement were ± 3 mm. Regarding the mode of delivery, the recommended cesarean section (rCS) group showed significantly smaller CV measurements (CV: 11.37 ± 0.73, p-value < 0.0001) than any other delivery group. No statistical difference in CV between the vaginal delivery and unplanned cesarean section groups was found (p-value 0.902). DT measurements only showed a significant difference between rCS and elective cesarean section (p-value 0.039). 134 incidental findings were noted.Conclusion Strong interobserver agreement irrespective of the reader’s experience level supports MR pelvimetry as a reliable method for identifying women with fetopelvic disproportion in breech presentation. For a comprehensive appraisal of incidental findings, radiologic expertise is vital.Key points: Citation Format
Keywords: MR pelvimetry; breech; obstetric; interobserver; reference value